Prescription medication use of United States military service members by therapeutic classification - Knapik, Joseph J.; Trone, Daniel W.; Steelman, Ryan A.; Farina, Emily K.; Lieberman, Harris R. (Frontiers in Pharmacology, 2022)
Background: This cross-sectional study investigated the prevalence of, and factors associated with, filled prescription medications (FPMs) among United States (US) service members (SMs). Methods: A stratified random sample of active duty SMs from the Air Force, Army, Marine Corps, and Navy was obtained from military workforce records. Participants (n = 26,680) completed a questionnaire on demographics, physical characteristics, and lifestyle factors and approved access to their FPM for the previous 6 months. FPMs were obtained from the military Pharmacy Data Transaction Service that included all prescription medications dispensed at military medical treatment facilities, abroad, at retail pharmacies in the US, and/or through mail-order programs. Results: About two-thirds (65%) of SMs had ≥1 FPM in the 6 months surveillance period. Central nervous system (CNS) agents had the highest prevalence (41%), followed by anti-infective agents (20%), eye/ear/nose/throat preparations (20%), gastrointestinal drugs (18%), autonomic drugs (17%), skin and mucous membrane agents (13%), antihistamine drugs (12%), respiratory tract agents (12%) and cardiovascular drugs (9%). Among CNS agents, overall prevalence of dispensed non-steroidal anti-inflammatory drug (NSAIDs) was 30%. The odds of any FPM was independently associated with female gender, older age, higher body mass index, former tobacco use (smoking and smokeless tobacco), lower alcohol consumption, and was highest among Army, lowest among Marine Corps personnel. Conclusion: In this sample of SMs, dispensing of prescription medication was high, especially NSAIDs, but dispensing of cardiovascular drugs was much lower compared to the general US population, likely because of the younger age and higher level of physical activity of SMs.